1998
DOI: 10.1093/ps/77.6.912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin E supplementation on lipid oxidation and volatiles content of irradiated, cooked turkey meat patties with different packaging

Abstract: A study was conducted to determine the effects of dietary vitamin E supplementation on the storage stability and volatiles production in irradiated cooked turkey meat. Turkeys, raised with diets containing 25, 50, 75, or 100 IU of dl-alpha-tocopheryl acetate (TA)/kg diet from 1 to 105 d of age, were fed with diets containing 25, 200, 400, or 600 IU of TA/kg diet from 105 to 122 d of age. Breast and leg meat patties were prepared, irradiated at 0 or 2.5 kGy dose, cooked to an internal temperature of 78 C, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 26 publications
1
33
0
2
Order By: Relevance
“…Our results were in agreement with the result reported on other kinds of antioxidant (such as a-tocopherol), which indicated that antioxidant might help retard the lipid oxidation and increase the shelf-life of irradiated pork (Sohn et al, 2009). Ahn et al (1998b) reported that TBARS in irradiated turkey breast gradually decreased as dietary tocopherol acetate level increased. Antioxidants can minimize irradiation-induced peroxidation of lard and tallow (Kyong et al, 1998;.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars) Valuessupporting
confidence: 92%
“…Our results were in agreement with the result reported on other kinds of antioxidant (such as a-tocopherol), which indicated that antioxidant might help retard the lipid oxidation and increase the shelf-life of irradiated pork (Sohn et al, 2009). Ahn et al (1998b) reported that TBARS in irradiated turkey breast gradually decreased as dietary tocopherol acetate level increased. Antioxidants can minimize irradiation-induced peroxidation of lard and tallow (Kyong et al, 1998;.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars) Valuessupporting
confidence: 92%
“…In the last decade, the interest on natural antioxidants and plant extracts to inhibit safety and negative consumer perception of synthetic antioxidants have been concerned. [9] Green tea is rich in flavonoids that have antioxidant properties. [10] Grape seed extracts contain large amounts of phenolic compounds and antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during storage of the frankfurters, hexanal increased more intensively compared to the other volatiles. Hexanal is reported to be the most sensitive indicator for lipid oxidation (Ahn et al, 1998). However, other lipidderived volatiles such as heptanal, octanal, and nonanal should also be taken into account due to their low flavour threshold values (Specht & Baltes, 1994).…”
Section: Discussionmentioning
confidence: 99%